The Relationship of Educabilty Motorcycles to Basic Technical Skills of Playing Futsal - Muhammad Fahmi Abdul Hakim; Tatang Muhtar; Dewi Susilawati (JUARA : Jurnal Olahraga, 2023)
This study aimed to analyze the relationship between motor educability and basic technical skills in playing futsal. This research was conducted at a futsal academy in the city of Bandung with a sample of students aged 15-18 years. The research method used is a quantitative research using descriptive correlation analysis. The results of the study show that (1) there is a significant relationship between motor educability and the basic technical skills of passing in playing futsal; (2) There is a significant relationship between motor educability and basic dribbling technical skills in playing futsal; (3) There is no significant relationship between motor educability and basic shooting technique skills in playing futsal.